Internalisasi Pendidikan Agama dalam Membentuk Masyarakat Madani - Dinil Abrar Sulthani (Tarbiyatuna: Jurnal Pendidikan Islam, 2021)
This paper discusses the phenomena and dilemmas of society that are selfish and ignore interactions with society. Sometimes the role of religious education is considered insignificant in overcoming every problem in society. Especially in eras of growing; information and technology, so that the internalization of the value of religious education is obscure. The purpose of this paper is to describe in full the concepts and values of religious education that are relevant to every condition of the era. Thus, the achievements of internalization of religious education can form civil society. This paper uses a literature study method, a qualitative approach with relevant references. The results of this paper state that religion can be a solution to every human problem. Religious education has an important position in every series of community activities. The conclusion of this paper is that civil society can be realized by internalizing the value of religious education; such as educational efforts, supervision, and friendship.